Proposal for a process management system for the Association of Community Women of the Tosagua Canton, Ecuador - Jiménez Navarrete, Danixa (2024)
A process management system is crucial for any company, because it allows the optimization of production and provides quality assurance. The main objective of the research is to propose a process management system for the Community Women's Association of the Tosagua canton, Ecuador. An interview and direct observation were applied to complete the investigation, which began with a detailed analysis of the existing processes in the organization, identifying their interactions, responsibilities and work flows. They proceeded to design them in a clearer and more efficient way. Roles and responsibilities were identified to ensure the traceability of activities, all in line, with the principles of transparency and participation typical of the Popular and Solidarity Economy. Then, the key processes of the association will be determined, such as production, administration and marketing. By having clear and detailed guidelines on the processes, training and understanding of the activities carried out in the association are facilitated, which contributes to strengthening the organizational culture and the performance of all staff.